The Effect of Electric Vehicle Deployment on Renewable Electricity Generation in an Isolated Grid System: The Case Study of Cyprus - Taliotis, Constantinos; Fylaktos, Nestor; Partasides, George; Gardumi, Francesco; Sridharan, Vignesh; Karmellos, Marios; Papanicolas, Costas N. (Frontiers in Energy Research, 2020)
Decarbonisation of national economies to mitigate climate change requires transformation of the entire energy system. Investments in renewable energy technologies in the electricity supply system are increasing, but substantial effort is called for in other sectors, such as transport. While European Union member states have submitted their integrated National Energy and Climate Plans, this paper focuses on partial electrification of the transport sector as a measure to reduce carbon dioxide emissions in the isolated grid system of Cyprus in a cost-effective manner. The present work assesses the impact of electric vehicle deployment on the share of renewable electricity generation, electricity costs and carbon dioxide emissions. Quantification of these aspects is provided with an outlook until 2035. A cost-optimisation model (OSeMOSYS) is used that takes into account the electricity supply, road transport, and heating and cooling sectors. Smart charging option is also evaluated as a possibility.